2014
DOI: 10.5089/9781475579772.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Bias and Accuracy in the World Bank-IMF's Debt Sustainability Framework for Low-Income Countries

Abstract: The World Bank and the IMF have adopted a debt sustainability framework (DSF) to evaluate the risk of debt distress in Low Income Countries (LICs). At the core of the DSF are empirically-based thresholds for each of five different measures of the debt burden (the "debt threshold approach" DTA). The DSF contains a rule for aggregating the information contained in these five different variables which we label the "worst-case aggregator" (WCA) in view of the fact that the DSF considers a breach of any one of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Recently Berg et al (2014) examined how the DSF uses and aggregates the information contained in five separate debt indicators, taking as given the KN-based probit regressions in the current DSF. They found that using debt thresholds, rather than probability thresholds, results in a loss of country-specific information that reduces accuracy of predictions.…”
Section: Crisesmentioning
confidence: 99%
“…Recently Berg et al (2014) examined how the DSF uses and aggregates the information contained in five separate debt indicators, taking as given the KN-based probit regressions in the current DSF. They found that using debt thresholds, rather than probability thresholds, results in a loss of country-specific information that reduces accuracy of predictions.…”
Section: Crisesmentioning
confidence: 99%
“…This approach relies on the Generalized Linear Model (GLM -typically the probit or logit version). Several studies use GLM to identify the determinants of fiscal crises, including Marashaden (1997), Detragiache and Spilimbergo (2001), Peter (2002), Manasse et al (2003), Ciarlone and Trebeschi (2005), Kraay and Nehru (2006), Gourinchas and Obstfeld (2012), Berg et al (2014), Dawood, Horsewood, andStrobel (2017), andPamies Sumner andBerti (2017). 10 Probit models also have an important role in policy practice, notably in the IMF/World Bank debt sustainability framework for low-income countries (see IMF, 2015).…”
Section: Past Attempts At Predicting Crisesmentioning
confidence: 99%
“…I also display receiver-operator characteristic curves which, for each possible probability cutoff, plot true positives against false positives. And I report the area under the receiveroperator characteristics curve (AUROC), a popular measure of how well the rankings of probabilities correspond to observed outcomes (see, e.g., Jorda et al (2011) or Berg et al (2014)). Intuitively, the AUROC captures the probability that an algorithm selects the crisis out of a randomly selected crisis and non-crisis case.…”
Section: Performance Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, the DSF has a limited ability to predict actual debt problems (IMF, : 7) . One possible change to address such failings is the more generalized introduction of a probabilistic approach (Berg et al., ) partially included for borderline cases after the DSF's 2012 review (IMF, ). The inclusion of more country‐specific variables in the underlying methodology that generates the risk rating — as opposed to relying on the broad averages of low‐income countries — seems sensible, although the complexity generated has raised concerns about usability (Martin, ), and the IMF () notes such variables were only sparsely utilized since the last review.…”
Section: Debt Sustainability Framework: Evolving But Not Quite Enoughmentioning
confidence: 99%